Rock Phosphate Enriched Compost vis-à-vis Inorganic Fertilization: Effect on Soil Chemical and Biological Properties - Sangma, Christy B.K.; Moharanna, P. C.; Biswas, D. R. (Indian Journal of Hill Farming, 2017)
An experiment was carried out at Soil Science farm in IARI, New Delhi to assess the effect of soil amendment with rice straw enriched rock phosphate compost on chemical and biological properties as compared to mineral fertilization. The four treatments applied were viz. T1: Control; T2: Recommended dose of NPK fertilizers (100% NPK); T3: Rice straw enriched rock phosphate compost @5t ha-1; T4: 50% NPK+ Rice straw enriched rock phosphate compost @5t ha-1. The soil samples from the above treatment plots were collected at 0-15 cm soil depth and analysis were carried out for chemical and biological soil properties as per the standard procedures. The chemical parameters like mineral nitrogen [ammonical (NH4) and nitrate (NO3)-N], available phosphorus (P), soil organic carbon (SOC) were found to be highest in the T4 treatment plots (P≤0.05). The soil biological properties like soil microbial biomass carbon (SMB)-C, -N and -P and enzyme activities like alkaline phosphatase (PHA), dehydrogenase (DHA), fluorescein di-acetate (FDA) and urease activity were also found to be significantly higher in integrated treatment of 50% of NPK+enriched compost plot as compared to the sole treatment either of enriched compost or inorganic fertilization. The significantly higher metabolic quotient (qCO2) in the treatment T2 i.e. 100% recommended doses of NPK (5.45 mg CO₂–Cg-1Cmic h-1; P≤0.05) indicate the negative effect on the microbial activity in the soils. Thus, from the present study it can be concluded that the 50% NPK+ Rice straw enriched rock phosphate compost treatment has the potential to enrich the soil with nutrients and at the same time can improved the microbial activities in the soil.